THE RELATIONSHIP OF STUDENT’S SELF-EFFICACY WITH MASTERY OF ARABIC LESSONS IN ONLINE LEARNING - Raudah Raudah; Nurul Wahdah; Yulia Rahmah; Mawada Elmeshad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to know the level of student self-efficacy, the level of subject mastery and the relationship between student self-efficacy and mastery of online Arabic lessons. This study used correlation research with a total of 154 respondents in 5 (five) Madrasah Aliyah Palangka Raya. Methods of data collection used questionnaires and documents. The results showed that: The average level of self-efficacy of students in learning Arabic online was 3.1911 which means the high category. The level of mastery of Arabic lessons in online learning is 7.2468, which means the medium category. There is a positive relationship between students' self-efficacy and mastery of online Arabic lessons which is classified as good with a sig p = 0.000 0.05. Self-efficacy will have a good influence on the results of mastery of lessons conducted online.